Calorimetriс and spectroscopic investigation of proflavine - salmon testes DNA binding - Khrebtova, A. S.; Dukhopelnykov, Ye. V.; Bereznyak, E. G.; GladkovskayaN. А.; Zinchenko, A. V. (Biophysical Bulletin)
The interaction of proflavine with salmon testes DNA is investigated by differential scanning calorimetry (DSC) and spectrophotometry in solutions with ionic strength I=0,02 M and I=0,1 M. We have applied the Scatchard formalism to analyze the spectrophotometric data. The thermodynamic melting parameters of DNA in the complexes with proflavine are obtained from DSC data. It is shown that proflavine forms two different types of complexes on DNA. The thermodynamic properties of double helix in these complexes are different. The complete thermodynamic profile for proflavine intercalation is obtained. Binding parameters for intercalation determined from calorimetric and spectrophotometric data are in a good agreement.